2016
DOI: 10.15386/cjmed-529
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitro-oxidative stress in the pathogenesis of experimental rat periodontitis

Abstract: Background and aimsPeriodontitis is a common chronic adult condition that implicates oxidative damage to gingival tissue, periodontal ligament and alveolar bone. This study aimed at assessing the association between the nitro-oxidative stress and the periodontal tissues destructions in experimental rat periodontitis.MethodsPeriodontitis was induced in 15 male albino rats by repetitive lesions to the gingiva adjacent to the inferior incisors, performed daily, for 16 days. On D1, D3, D6, D8, and D16 the onset an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…For morphometric analysis, the images were digitized using the Leica Biosistems ® Digital Image Hub online software (Wetzlar, Germany). The study variables were determined: thickness and structure of the epithelium, state of the basal membrane, quantitative measurement of the inflammatory area and the condensation of the connective tissue, according to the criteria described by authors such as Camacho-Alonso et al [23], Bosca et al [24] and Ionel et al [25].…”
Section: Pathological Anatomymentioning
confidence: 99%
“…For morphometric analysis, the images were digitized using the Leica Biosistems ® Digital Image Hub online software (Wetzlar, Germany). The study variables were determined: thickness and structure of the epithelium, state of the basal membrane, quantitative measurement of the inflammatory area and the condensation of the connective tissue, according to the criteria described by authors such as Camacho-Alonso et al [23], Bosca et al [24] and Ionel et al [25].…”
Section: Pathological Anatomymentioning
confidence: 99%
“…In such a rat model, it was shown that periodontitis leads to an increased production of reactive oxygen species and markers of oxidative damage (Ekuni et al, 2010 ). In addition, oxidative stress induced by periodontitis seems to be associated with the dynamics and severity of the periodontal inflammation (Bosca et al, 2016 ).…”
Section: Animal Experimentsmentioning
confidence: 99%
“…The results also revealed that the rats fed a high-fat diet and HW, compared with the HFD rats showed a lower distance between the CEJ-ABC and a greater BT/TV. Gingival oxidative stress is involved in the progression of alveolar bone resorption [ 11 , 12 ]. Suppression of obesity by drinking HW may attenuate alveolar bone resorption by limiting gingival oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that oxidative stress stimulates osteoclast differentiation [ 7 , 8 ]. Animal studies have also suggested that oxidative stress is involved in the progression of alveolar bone resorption [ 9 , 10 , 11 , 12 ]. In a recent review, the basis for the relationship between obesity and periodontitis lies at a fundamental intracellular level, which includes oxidative stress [ 13 ].…”
Section: Introductionmentioning
confidence: 99%